2020
DOI: 10.3389/fcimb.2020.00243
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Reactive Oxygen Species and the Inflammasome Are Crucial for Restriction of Neospora caninum Replication

Abstract: Neospora caninum poses as a considerable threat to animal health and generates significant economic impact in livestock production worldwide. Here, we have investigated the mechanism that underlies the participation of the inflammasome complex and Reactive Oxygen Species (ROS) in the regulation of immune responses during N. caninum infection. For that purpose, we used in vitro (bone marrow derived macrophages) and in vivo mouse models of infection. Our results show that NLRP3 and NLRC4 receptors, alongside wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…The reasons for this difference remains to be determined, but a possible explanation may rely on distinct cellular sources or distinct mechanisms of IL1-β secretion depending or not on the activation of the inflammasome 60 . In the murine model, others have shown that only live parasites, and not heat attenuated or fixed N. caninum parasites or antigens , were able to induce IL-1β production by bone marrow-derived macrophages 61 . It would be interesting to assess in the future the cellular sources of IL-1β production in bovine adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this difference remains to be determined, but a possible explanation may rely on distinct cellular sources or distinct mechanisms of IL1-β secretion depending or not on the activation of the inflammasome 60 . In the murine model, others have shown that only live parasites, and not heat attenuated or fixed N. caninum parasites or antigens , were able to induce IL-1β production by bone marrow-derived macrophages 61 . It would be interesting to assess in the future the cellular sources of IL-1β production in bovine adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, NLRP3 inflammasome is indirectly activated by cell disturbances caused by particulate material or pathogens. Increasing evidence in the literature demonstrate the participation of NLRC4 in inflammatory pathologies and non-bacterial infections [7][8][9][10][11][12][13][14][15][16]. The mechanisms involved in NAIP/NLRC4 activation under these conditions are still unknown, opening the possibility that endogenous signals could modulate NLRC4 activation in some circumstances, similarly to described for NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…NAIP/NLRC4 inflammasome is one of the best-characterized inflammasomes and has an important role in the restriction of intracellular pathogenic bacteria, such as Salmonella typhimurium [4,5] and Legionella pneumophila [6]. Importantly, recent studies have demonstrated a role for NAIP/NLRC4 inflammasomes in response to non-bacterial infections [7][8][9][10] and sterile inflammation triggers [11][12][13][14][15][16]. However, the molecular mechanism of NAIP/NLRC4 activation under these conditions remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In neosporosis, the role of ROS has been scarcely studied and remains controversial. Despite it has been suggested that ROS and its signaling pathway are crucial in the resistance against N. caninum infection both in vivo and in vitro (da Silva et al, 2017; Mota et al, 2020), a recent report by Tao et al (2022) a rmed that increased ROS levels triggered by the infection were associated with mitochondrial damage in caprine endometrial epithelial cells in vitro, potentially contributing to the pathophysiology of abortion. Taking into account that the role of OS in the placenta of N. caninum infected animals remains unexplored, the aim of the present report was to investigate OS markers, endocrine and immune changes in the placenta of pregnant mice experimentally infected with N. caninum.…”
Section: Introductionmentioning
confidence: 99%